Preclinical development of anti-BCMA immunotoxins targeting multiple myeloma - Shancer, Zoe (Antib Ther, 2018)
BACKGROUND: Multiple myeloma (MM) is a B-cell malignancy that is incurable for the majority of patients. New treatments are urgently needed. Recombinant immunotoxins (RITs) are chimeric proteins that are composed of the Fv or Fab portion of an antibody fused to a bacterial toxin. B-cell maturation antigen (BCMA) is a lineage-restricted differentiation protein and an ideal target for antibody-based treatments for MM. METHODS: RITs were produced by expressing plasmids encoding the components of the anti-BCMA RITs in Escherichia coli followed by inclusion body preparation, solubilization, renaturation, and purification by column chromatography. The cytotoxic activity of RITs was tested in vitro by WST-8 assays. We also measured their binding to human and mouse serum albumins and to BCMA and measured their serum half-life in mice. RESULTS: Using Fvs from different anti-BCMA antibodies, we produced RITs that specifically kill BCMA-expressing MM cells in vitro. To increase the serum half-life in vivo, we generated RITs that are fused with albumin-binding domains (ABDs). All RITs with ABDs have some decreased activity compared to the parent RIT, which is not due to decreased binding to BCMA. CONCLUSIONS: Various new anti-BCMA immunotoxins were produced and evaluated. None of these were better than LMB-75 (anti-BCMA BM306-disulfide-stabilized Fv-LRggs) supporting the further preclinical development of LMB-75.